Analisis pendapatan dan proporsi bagi hasil nelayan Kurungkuru di Kelurahan Sukanayo Kecamatan Kokalukuna Kota Baubau - Sardiana; La Ola, La Onu; Nurdiana A; Kamri, Syamsul; Riani, Irdam; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2022)
The “kurungkuru” fishing gear is a traditional gear that similar to trap boat and consideres as a type of lift net that requires fishing aids in the form of lights to carry out fishing operations. This study aims to determine how much profit is obtained by the fishermen of Kurungkuru and the proportion of profit sharing applied in Sukanayo Village, Kokalukuna District, Baubau City. This study uses a survey method with a sample of 16 fishermen from a total population of 27 fishermen. This research was conducted during the period of April and May 2021. The types of data used were primary data (identity of respondents, investment costs, fixed costs, variable costs, production amount, types of catch, price level and profit sharing proportion) and secondary data (characteristics of the local community, education level, number of villagers). Data were collected using interview, questionnaire, documentation and literature studies. The data analyzed are the amount of costs incurred, the amount of revenue and profits which are analyzed using cost analysis, revenue analysis, and profit analysis. The catches of kurungkuru in Sukanayo Village are anchovies, tembang fish and kite fish. The results showed that the highest profit of IDR39,438,444 and the lowest profit of IDR 14,766,500. The profit-sharing system applied by fishermen who own the gear waa equally divided or 50:50, meaning that the gear owner got a 50% profit and the other 50% for the crew, The profit distribution was given to parents 2 share, adults 1.5 share, and teenage children 1 share. The largest share was given to parents where the distribution was based on dependent ownership.